Innovative Technique of Segmentation and Feature Extraction for Melanoma Detection - Singh, A; Maurya, R; Yadav, R; Srivastava, V (International Journal of Computer Sciences and Engineering, 2025)
This paper presents a new technique of segmentation and feature extraction for classification of melanoma and non-melanoma. Both segmentation and feature extraction is done by the concept of average value since average is the number closer to every number. Here we have also compared K-means segmentation technique with new the technique. In experimental part we evaluate 80.897% average accuracy through neural network classification.